Whole-exome sequencing of 228 patients with sporadic Parkinson's disease. - Sandor, C; Honti, F; Haerty, W; Szewczyk-Krolikowski, K; Tomlinson, P; Evetts, S; Millin, S; Keane, T; McCarthy, S; Durbin, R; Talbot, K; Hu, M; et al. (Nature Publishing Group, 2017)
Parkinson’s disease (PD) is the most common neurodegenerative movement disorder, affecting 1% of the population over 65 years characterized clinically by both motor and non-motor symptoms accompanied by the preferential loss of dopamine neurons in the substantia nigra pars compacta. Here, we sequenced the exomes of 244 Parkinson’s patients selected from the Oxford Parkinson’s Disease Centre Discovery Cohort and, after quality control, 228 exomes were available for analyses. The PD patient exomes were compared to 884 control exomes selected from the UK10K datasets. No single non-synonymous (NS) single nucleotide variant (SNV) nor any gene carrying a higher burden of NS SNVs was significantly associated with PD status after multiple-testing correction. However, significant enrichments of genes whose proteins have roles in the extracellular matrix were amongst the top 300 genes with the most significantly associated NS SNVs, while regions associated with PD by a recent Genome Wide Association (GWA) study were enriched in genes containing PD-associated NS SNVs. By examining genes within GWA regions possessing rare PD-associated SNVs, we identified RAD51B. The protein-product of RAD51B interacts with that of its paralogue RAD51, which is associated with congenital mirror movements phenotypes, a phenotype also comorbid with PD.